Effectiveness of Social Skills Training to Reduce Students Aggressive Behavior - Aryani, Farida; Kasim, Sinta Nuru Oktaviana (Universitas Negeri Makassar, 2021)
This study was conducted to examine the effectiveness of social skills training to reduce students aggressive behavior in the city of Makassar. This study uses 20 participants (students) from the four faculties, which are Faculty of language and literature, Faculty of Art and Design, Faculty of Engineering, and faculty of sports in the UNM. This study uses a pre-experimental design and data analysis by using t-test. The results showed that the level of aggressiveness of 20 students during the pretest in at the high category, but after being given the social skills training the level is in the low category. In addition, it shows that social skills training is effective in reducing aggressive behavior of students. The results showed that social intelligence training which includes training materials, namely (1) to train students self-consciousness (self-awareness), (2) how to express feelings, (3) students etiquette , (4) time management, and (5) conflict management to reduce students aggressive behavior at UNM. The implications of this study are that to reduce students conflict at UNM, then social skills training should be used as patterns for new student orientation for all students in all faculties at UNM.